Discurso materno, psicose e psicanálise: travessias... - Soares, Maria Zilda Silva (2015)
Grounded in the perspective of psychoanalysis as a scientific investigation field, a tool for qualitative research, a way of comprehending the psychism, a form for appropriating the unconscious speech and a science of singularity, the present study aims to understand the actuality of theoretical constructs formulated by Freud, Lacan and Aulangnier regarding psychoses, in correlation with reports from mothers diagnosed as psychotic. Such reports were collected through psychoanalytical interviews, which enabled the listening and recording of accounts of two mothers, named Joana and Barbara, both from northeast Brazil, regarding their experiences, as well as their relations with their children, who are also diagnosed as psychotic. The process in comparing the theory and the subjects life experience, in the present thesis, has occurred according to the following question: how do their speeches apply and/or correlate with theoretical considerations formulated by Freud, Lacan and Aulagnier? By listening to Joana s and Barbara s maternal reports of their life stories, including childhood, youth, loving relationships, marriage, pregnancy, maternity and experiences with their children diagnosed as psychotic, we managed to make some correlation with the following psychoanalytical concepts: Oedipus Complex and Castration, Femininity, Identification, Language, Significant, Historic Reality, Psychotic Potency and Name-Of-The-Father Foreclosure. Maternal speech and theory intertwined and led to some important interpretations: the subjective dynamic of the interviewed mothers, including the Oedipal, the process of feminine sexuality, identifications, historic reality, loving relationships with husbands, paternal role, quality of investment and will for pregnancy and maternity, were crucial in order to understand a sort of short circuit in the psychodynamics of a family which has developed a psychosis. Therefore, the conflict between ego and reality, present in psychoses, the lack of symbolization of paternal law or the Name-Of-The-Father foreclosure and the psychotic potency derive from mismatches manifested amongst the maternal and paternal roles and the care of the child